Oil spill effects in biota and traditional populations from protected areas of Brazil's Northeast - Mello, Luiza Costa; Cavalcante, Rivelino Martins; Bastos, Luciana Machado; Nossol, Arlene Bispo dos Santos; Martins, Mario Machado; Cesar-Ribeiro, Caio [UNESP]; Pauly, Guacira de Figueiredo Eufrasio [UNESP]; Abessa, Denis Moledo de Souza [UNESP] (Taylor & Francis Inc, 2025)
In 2019, more than 3000 km of the Brazilian coast was severely affected by an oil spill of unknown origin. The present study evaluated the ecological impacts and toxicological health risks for traditional communities from two protected areas affected by oil: the Environmental Protection Area of Canoa Quebrada (EPACQ) and the Marine Extractive Reserve of the Parna & iacute;ba Delta (MERPD). Sediment and marine organisms were sampled, including the bivalve Mytella charruana, crab Ucides cordatus, and catfish Sciades herzbergii, and analyzed for PAH concentrations and human health risks. The soft tissues were analyzed for lipoperoxidation (LPO) and DNA damage. MERPD bivalves and fish exhibited higher LPO and DNA damage levels, whereas no significant differences were observed in crabs. PAHs' bioaccumulation was higher in fish and bivalves from MERPD, whereas in crabs, higher contamination occurred in EPACQ. Crab, fish, and shellfish from EPACQ had more carcinogenic compounds representing health risk; however, no statistical differences were found between the two study areas. The present study highlights the interconnectivity of ecosystems post-oil spills, emphasizing the need for holistic approaches to perform an integrated risk assessment of ecological and human health impacts to provide a comprehensive view of post-2019 challenges.
Keywords: Bioaccumulation; biomarkers; hydrocarbons; health risk